Karakterisasi Morfologi Sukun (Artocarpus altilis Forb.) Di Desa Ohoitahit Dan Danar Kepulauan Kei Kecil Kabupaten Maluku Tenggara - Reniwurwarin, Amat; Laisina, Jane K J; Wahditiya, Andi A (Jurnal Agrosilvopasture-Tech, 2024)
This study aims to characterize the morphology of breadfruit (Artocarpus Altilis Forb.) In Ohoitahit Village and Danar Kecil Kecil Kecil Southeast Maluku. The sampling method through two sample units, namely key informants and target plant accessions. Key informants are community leaders who have in -depth knowledge about the genetic diversity of breadfruit in the village that is used as a sample. Target plant accessions are a variety of varieties of identification of key informants. Withdrawal of samples for critical informants is carried out by snowball sampling methods, while target plant accessions are selected using accidental sampling methods (accidental sampling) or intentional sampling (purposive sampling). Data presentation using descriptive methods. The results showed a significant morphological diversity in breadfruit in the Kei Islands. There is a diversity of morphology in breadfruit based on 31 observation variables. In the character of the tree, there is diversity, among others, the tree's shape, the trunk's surface, the branching pattern, and the direction of growing. In the leaf character there is diversity, namely the color of the leaf, the tip of the leaf, the length of the leaf strands, and the width of the leaf strands, and on the tip of the leaf. Flower characters have a diversity that is, the color of male flowers, male flower positions, and female flower positions. Fruit character has diversity is the shape of the fruit, the texture of the fruit skin, the sap on the skin, the skin color of the fruit, the length of the fruit, the weight of the fruit, and the fruit yield.